Los símbolos de la sostenibilidad ambiental en las creencias religiosas iraníes haciendo énfasis en el Zoroastrismo y el Islam - Ossadat Hejazi, Moeine; Sarbakhshian, Behnam (Innovaciencia, 2019)
Environmental issues have always been one of the main axes of sustainable development and the main challenges of the governments. The thing that has caused the most damage to nature is the over-exploitation of man from nature with modernist perspectives. It seems that human beings have a more peaceful, environmentally friendly attitude in the frameworks of traditional views. The two Zoroastrian and Islamic religions have had significant effects on Iranian thought since the beginning of the formation of powerful ancient and historical powers in Iran. Religions have used symbolic languages to express the deep concepts and the induction of internal effects. This study used a descriptive-historical method to identify the symbols related to environmental in indigenous culture and dominant religious beliefs in Iran. The data was collected using documentary research method. The research findings indicate that symbols can be categorized in six major groups including; symbols of sky, wind, and celestial bodies: 1- moon, stars, sun and planets, 2- mountain, soil, rock, cave, desert, 3- water, river, fountains, 4- plants: flowers, trees, 5- animals, 6- fire and light. There is a close relationship between Zoroastrian and Islamic beliefs toward elements of nature, in which respect for nature is considered as religious duties. Various symbols have emerged because of these beliefs in Iranian culture that have the ability to capture cultural, literary and artistic realms, sustainable architecture and urbanization on a regional, national, and international scale in order to preserve and restore the environment.